KONSEP DAKWAH NIR-RADIKALISME PERSPEKTIF SYAIKH ALI MAHFUDZ - Muhamad Agus Mushodiq; Muhammad Sulthon (Dakwah: Jurnal Kajian Dakwah dan Kemasyarakatan, 2020)
AbstractThis article aims to explore the concept of non-radicalism dakwah initiated by Ali Mahfudz. In analyzing the data, the researcher used the non-radicalism da'wah indicator formulated by Yusuf al-Qaradawi. The results of this study are: (1) the concept of preaching non-radicalism is manifested through three major conceptions, namely mauidzah (tadzkir and qissah), isryad, and khitabah; (2) a preacher must balance the use of revelation and reason; (3) in khilafiyah matters, Ali Mahfudz only explains it, without forcing readers to become fanatical about one understanding; (4) permits the use of israiliyyat as material for preaching; (5) the dynamism in his preaching is thought to have been caused by the transformation of his religious experience from the syafi'i school to the Hanafi school. AbstrakArtikel ini bertujuan untuk mengeksplorasi konsep dakwah non radikalisme yang digagas oleh Ali Mahfudz. Dalam menganalisis data, peneliti menggunakan indikator dakwah non radikalisme yang dirumuskan oleh Yusuf al-Qaradawi. Hasil penelitian ini adalah: (1) konsep dakwah non radikalisme diwujudkan melalui tiga konsepsi besar, yaitu mauidzah (tadzkir dan qissah), isryad, dan khitabah; (2) seorang da'i harus menyeimbangkan penggunaan wahyu dan akal; (3) dalam hal-hal yang bersifat khilafiyah, Ali Mahfudz hanya menjelaskan saja, tanpa memaksa pembaca menjadi fanatik terhadap satu pemahaman; (4) mengizinkan penggunaan israiliyyat sebagai bahan dakwah; (5) dinamisme dalam dakwahnya diduga disebabkan oleh transformasi pengalaman religiusnya dari mazhab Syafi'i ke mazhab Hanafi.